2019
DOI: 10.1111/nicc.12465
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between stressors and intensive care unit experiences

Abstract: Background Patients in intensive care units (ICUs) face many physical and psychological stressors because of the environment of these units and their own critical conditions and experience stress in various degrees. Each stressor may affect patients' experiences in ICUs differently. Aim and objectives This study aimed to examine the relationship between stressors and patients' experiences in an ICU. Methods This descriptive, cross‐sectional study was conducted between September 2014 and June 2015 in a universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…A first inspection of studies from different decades may give preliminary insights that can inform further detailed analyses of this topic. Three studies from different decades enable a first comparison of stressor ranking lists: the pioneering study of Cochran & Ganong (1989) [3], the study of Biancofiore et al (2005), which had been published 16 years later [33], and the most recent study of Zengin et al (2020) [63] (for details, see Supplementary Table S1). On the one hand, each ranking list contains stressors among the 10 highest ranking items that are not included in the other lists.…”
Section: Implications For Clinical Research and Practicementioning
confidence: 99%
See 1 more Smart Citation
“…A first inspection of studies from different decades may give preliminary insights that can inform further detailed analyses of this topic. Three studies from different decades enable a first comparison of stressor ranking lists: the pioneering study of Cochran & Ganong (1989) [3], the study of Biancofiore et al (2005), which had been published 16 years later [33], and the most recent study of Zengin et al (2020) [63] (for details, see Supplementary Table S1). On the one hand, each ranking list contains stressors among the 10 highest ranking items that are not included in the other lists.…”
Section: Implications For Clinical Research and Practicementioning
confidence: 99%
“…The larger item number of these domains is also a result of the finding that the ranking lists of patients, HCPs and relatives contain more physical and mental health stressors than communication and environmental stressors (Table 2). However, we have to take into consideration that some studies showed moderate to large associations between perceived environmental and communication stressors on the one hand and mental distress on the other hand, even when the stress level of the environmental and communication stressors were relatively low [10,63]. Moreover, there is ample evidence that perceived communication stressors and objectively measured environmental stressors can cause subjective mental distress, and that a reduction of environmental and communicative stress level leads to an improvement in mental distress [11,50,54,65,67,71,72,79,80].…”
Section: Implications For Clinical Research and Practicementioning
confidence: 99%
“…What does this paper contribute to the wider global clinical community? While thirst is one of the most intensely perceived symptoms, the second most prevalent symptom in ICUs [ 13 ], there is a lack in nursing research regarding its assessment, diagnosis, and interventions. There is a high prevalence of thirst among ICU patients (76.1% of subjects, median 5.37).…”
Section: Impact Statementmentioning
confidence: 99%
“…Identification of patients at risk and early intervention should be standard practice within ICUs [ 8 , 9 ]. The relevance of the topic does not emerge in medical and nursing literature, but the scientific debate needs to focus on thirst in ICU patients: in fact, while thirst is one of the most intensely perceived symptoms, the first [ 12 , 13 ] or the second [ 14 ] most prevalent symptom in ICUs, there is a lack in ICU nursing research regarding its assessment, correlation to patient deterioration, or to agitation state, diagnosis, and interventions. This is remarkable, as thirst is primarily identified by nurses within hospitals [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Understanding stressors experienced by critical care patients is also crucial. Zegnin and colleagues, in a cross‐sectional survey, examined the relationship between ICU‐experienced stressors in adults in an ICU in Turkey. Using the Intensive Care Experiences Scale and another scale they collected data on 116 adults who stayed more than 24 hours in an ICU.…”
mentioning
confidence: 99%